Nanostructural characterizations of graphite waste from French gas-cooled nuclear reactors and links with 14C inventory. (August 2016) - Pageot, J.; Rouzaud, J.-N.; Gosmain, L.; Deldicque, D.; Comte, J.; Ammar, M.R.
Abstract: For several decades, graphite has been used in French gas-cooled nuclear reactors as a neutron moderator and reflector. To better understand the impact of neutron irradiation on the organization of such a material, Raman microspectrometry and transmission electron microscopy were combined following an original approach. After neutron irradiation, lamellar crystalline nuclear graphite becomes a heterogeneous carbon–carbon composite composed of degraded (structurally and nanostructurally) and quasi-preserved phases. In the most degraded areas, the graphene layers become very small, completely mutually disoriented, and curved, forming nanometer-sized holes that contribute to a nanoporous nanostructure. Thus, these structural and nanostructural evolutions are closely related. At the micrometer scale, lamellar particles become very crumpled. Ultimately, with neutron irradiation, not only is the structure affected but the nanostructure is also deeply and heterogeneously modified. This is a new, significant finding. In addition, an important and original result of our work is the correlation of structural defects with the 14 C level. Moreover, the presence of nanoporous nanostructure may be related to the significant 14 C level increase from a certain neutron fluence. Thus, our study suggests that a significant part of 14 C could be localized in the nanoporous areas. From this hypothesis, various waste management solutions can be imagined.